Evaluasi Pelayanan Kefarmasian dan Penggunaan Obat Berbasis Standar Akreditasi di Instalasi Farmasi RSUD Sawerigading Kota Palopo - Nurul Rezkyah; Ervianingsih Ervianingsih; Yusnidar Yusnidar (LPPM Hang Tuah Pekanbaru, 2023)
Pharmaceutical services and drug use (PKPO) is one of the most important parts of a service to patients. Pharmaceutical services aim to identify, prevent, and resolve problems related to medication. Accreditation is an assessment of the Hospital Accreditation Committee (KARS) as an effort to improve the quality of services in hospitals. The research was conducted to see the level of conformity of the seven existing PKPO standards in the 2018 SNARS. The research was analyzed qualitatively and quantitatively. Quantitative data was collected using a questionnaire, and qualitative data were collected by interviewing the head of the Installation to support the answers to the questionnaire. The research subjects consisted of pharmacists and TTK. The results of the study show that pharmaceutical services and drug use (PKPO) at the Pharmacy Installation of Sawerigading Hospital in Palopo City in 2022 as a whole have met the requirements for the National Hospital Accreditation Standard (SNARS). The results were PKPO 1 Organizing (100%), Head of the installation, said that the hospital had set rules regarding organizing pharmaceutical services and drug use. PKPO 2 Selection and Procurement (100%), UDD (Unit Dose Dispensing) services have been running for all patients in the inpatient depot. PKPO 3 Storage as much as (83%), narcotics and psychotropics are stored in an alphabetical system, FIFO and FEFO. PKPO 4 Prescribing and Copying (89%), there are individuals who are competent in their fields and focus on clinical pharmacy. PKPO 5 Preparation and delivery (81%), the process of preparation and delivery of drugs has been carried out in accordance with the hospital's SOP. PKPO 6 Drug Administration (87%), there are limits to individual authority in administering drugs. and PKPO 7 Monitoring (91%), the monitoring process in patients is active.